2012
DOI: 10.1016/j.neuron.2012.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain GABAergic Neuron Precursors Integrate into Adult Spinal Cord and Reduce Injury-Induced Neuropathic Pain

Abstract: Neuropathic pain is a chronic debilitating disease characterized by mechanical allodynia and spontaneous pain. Because symptoms are often unresponsive to conventional methods of pain treatment, new therapeutic approaches are essential. Here, we describe a strategy that not only ameliorates symptoms of neuropathic pain, but is also potentially disease modifying. We show that transplantation of immature telencephalic GABAergic interneurons from the mouse medial ganglionic eminence (MGE) into the adult mouse spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
203
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(219 citation statements)
references
References 55 publications
(74 reference statements)
15
203
1
Order By: Relevance
“…However, the basic culture conditions for growing neurons in vitro have not been updated to reflect fundamental principles of brain physiology. Currently, most human neuronal cultures are grown in media based on DMEM/F12 (4,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), Neurobasal (25)(26)(27)(28)(29)(30), or a mixture of DMEM and Neurobasal (DN) (31)(32)(33)(34). To promote neuronal differentiation and survival, a variety of supplements, such as serum, growth factors, hormones, proteins, and antioxidants, are typically added to these basal media.…”
mentioning
confidence: 99%
“…However, the basic culture conditions for growing neurons in vitro have not been updated to reflect fundamental principles of brain physiology. Currently, most human neuronal cultures are grown in media based on DMEM/F12 (4,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), Neurobasal (25)(26)(27)(28)(29)(30), or a mixture of DMEM and Neurobasal (DN) (31)(32)(33)(34). To promote neuronal differentiation and survival, a variety of supplements, such as serum, growth factors, hormones, proteins, and antioxidants, are typically added to these basal media.…”
mentioning
confidence: 99%
“…While the precise mechanisms underlying this state are still being explored, it is believed that impairments in spinal cord dorsal horn inhibitory circuits, including the loss of GABAergic interneurons, is one of the major reasons for persistent neuropathic pain following nerve injury (Braz et al, 2012). In the spinal cord, local interneurons and descending inhibitory circuits modulate pain sensations that are processed in the superficial layers of the dorsal horn.…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
“…Overall, this study showed the beneficial effects of GABA-ergic NPC grafting in attenuating neuropathic pain resulting from peripheral nerve injury. Another study examined the effects of grafting of GABA-ergic progenitors from E12.5-13.5 mouse MGE into the lumbar spinal cord segments of mice displaying neuropathic pain following spared sciatic nerve injury (Braz et al, 2012, Table 2), which was accomplished through transection of two of the three terminal branches of the sciatic nerve. This study showed that GABA-ergic cell grafting reversed mechanical hypersensitivity but not inflammatory pain.…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence in support of this used mouse ES cell-derived MGE cortical inhibitory precursor cells, which were transplanted into a mouse model of peripheral sciatic nerve injury. 23 Using ES cell-derived MGE cells that expressed GFP under the control of the Gad1 promoter, it was demonstrated that the ES cell-derived MGE grafts adapted and thrived in the novel spinal cord environment and migrated throughout the ipsilateral dorsal and ventral horns. Within two weeks of transplantation the grafted cells showed immunocytochemical evidence of differentiation towards a neuronal phenotype (NeuN+) and likewise demonstrated immunoreactivity for markers of cortical GABAergic interneurons, namely GABA, neuropeptide Y, parvalbumin and somatostatin.…”
mentioning
confidence: 99%